2013
DOI: 10.1002/ijc.28655
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea consumption, genotype-basedCYP1A2andNAT2activity and colorectal cancer risk-Results from the EPIC cohort study

Abstract: Coffee and tea contain numerous antimutagenic and antioxidant components and high levels of caffeine that may protect against colorectal cancer (CRC). We investigated the association between coffee and tea consumption and CRC risk and studied potential effect modification by CYP1A2 and NAT2 genotypes, enzymes involved in the metabolization of caffeine. Data from 477,071 participants (70.2% female) of the European Investigation into Cancer and Nutrition (EPIC) cohort study were analyzed. At baseline (1992–2000)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…After the initial screening, based on the titles and abstracts, 317 articles remained for further full-text assessment. After retrieving the full-text review for detailed evaluation, 19 prospective cohort studies [13–31] examining the association between coffee consumption and colorectal cancer risk were identified. The results of the literature research and selection are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the initial screening, based on the titles and abstracts, 317 articles remained for further full-text assessment. After retrieving the full-text review for detailed evaluation, 19 prospective cohort studies [13–31] examining the association between coffee consumption and colorectal cancer risk were identified. The results of the literature research and selection are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies assessed the coffee consumption without using a specific dietary assessment method, and the rest of studies assessed coffee consumption with food frequency questionnaires (FFQ). Three studies investigated the associations of both caffeinated and decaffeinated coffee consumption with colorectal cancer risk [19, 28, 31]. Four studies assessed the association of coffee consumption with colon cancer risk by anatomical sites [18, 27, 28, 31].…”
Section: Resultsmentioning
confidence: 99%
“…The association between the rs11202607 polymorphism in the phosphatase and tensin homolog (PTEN) gene, and CRC was stronger in never tea drinkers suggesting cooperative interactions between tea, PTEN and CRC development [125], but the overall GT effect on cancer incidence was weak. No correlation was found for the GT modulation of NAT and CYP4501A2 expression in Caucasians [92]. Despite the negative in vitro studies some authors claimed an independent protective effect of GT on CRC incidence ( [117,[123][124][125], Table 3), they assume that GT drinking may be a cofactor rather than the causal prevention agent for CRC.…”
Section: Crc-association Studiesmentioning
confidence: 95%
“…For CRC and tea intake, cohort and case controls studies from Europe [92][93][94][95][96][97] and the USA [98][99][100][101][102][103] often did not specify the type of tea; since in these countries black tea is prevalent, it can safely be assumed that these studies cover black tea. Other studies calculated and quantified the amount of flavonoids from all food sources.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…The following papers were excluded: four GWAS (Cornelis et al, 2011;Sulem et al, 2011;Amin et al, 2012;Rodenburg et al, 2012); four studies lacking coffee intake analysis (Sachse et al, 1999;Basvi et al, 2007;Ghotbi et al, 2007;Gunes et al, 2009); eight studies not providing coffee intake data according to rs762551 genotypes (Goodman et al, 2003;Kotsopoulos et al, 2009;Hallström et al, 2010;Schmidt et al, 2010;Guessous et al, 2012;Josse et al, 2012;Palatini et al, 2015;Yamamoto et al, 2015); two studies providing CC and combined AC + AA genotypes counts instead of AA and AC + CC genotype counts (Palatini et al, 2009;Pavanello et al, 2010); two studies using patient samples (Cornelis et al, 2007;Bågeman et al, 2008); and one study with a small sample size . Finally, 12 studies were included in the meta-analysis (Nordmark et al, 2002;Sata et al, 2005;Cornelis et al, 2006;Kotsopoulos et al, 2007;Tan et al, 2007;Jernström et al, 2008;Djordjevic et al, 2010;Popat et al, 2011;Kohno et al, 2013;Lowcock et al, 2013;Tian et al, 2013;Dik et al, 2014) (Figure 1). The study characteristics are shown in Table 1.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%